ESTIMATION DES DEBITS DU FLEUVE OUEME A L’EXUTOIRE DE AHLAN A PARTIR DE DEUX MODELES HYDROLOGIQUES POUR LA PREVISION DES CRUES - BRICE, MONGBO F. A.; ERNEST, AMOUSSOU; PLACIDE, CLEDJO F. G. A. (Advances in Social Sciences Research Journal, 2020)
The river Oueme is the longest river in Benin with a watershed covering more than 40% of the country’s surface. The hydrological regime of the river Oueme is irregular and is characterized by an alternation of strong floods and severe low water. The morphodynamics of the study area from the source to the Ahlan outlet favored rapid flows in the basin. Thus, we are witnessing a recurrence of flooding in the delta. A rainflow- rainflow and rainfall- rainflow modeling was set up to develop a tool for estimating the flows required for the sizing of the structures. It emerges from these results that the rainfall- rainflow and rainflow-rainflow models presented Nash values ​​greater than 0.90 both in setting and in validation. Which testifies to the efficiency of the models. However, for this work, the rainfall-runoff model was chosen because of the relatively longer learning time. From these results, a management tool was developed for the recovery of water from overflows in the basin for economic purposes.